BUSINESS PROCESSES RECONFIGURATION THROUGH THE IMPLEMENTATION OF AN ENTERPRISE RESOURCE PLANNING SYSTEM - Jesus, Cristiano; Lima, Rui (Journal of Applied Engineering Science, 2021)
The use of technology in organizations does not always produce the expected effects, because the cause-effect relationship in efficiency, productivity and therefore competitiveness is not linear. The available resources, ways of access and their capacities in terms of storage, processing and speed of response are known, however they are not always assimilated by the agents of the productive sector as they should to promote effective results and business agility. The research procedure adopted was a critical-descriptive analysis of a real case. Based on the bibliographic review on Business Processes reconfiguration and follow-up of an implementation project in a Brazilian company, a Business Model reconfiguration with ERP system implementation case was described and evaluated. The purpose of this article is to present a success case of Information Systems implementation project, to demonstrate the long way to go before reaching the results that makes such a project a successful project and to examine the impacts in the human resource perception. The research resulted in the description of an ERP implementation case, its evaluation based on perceptions, followed by critical discussion about barriers and risks inherent to projects of this nature. Although information technology has advanced a lot in the last decades in resources and functionalities, its cost has been significantly reduced, and its acquisition has been greatly facilitated, implementation is not a trivial activity. The article can serve as a guide for characterization of risks and sensitive aspects in reconfiguration projects for organizations that wish to achieve effectiveness in this type of project.